La frontière des métiers dans le monde antique - Carl-Loris Raschel (Frontière·s)
This paper is an attempt to discuss the use and the variations of the meaning of the term ‘gens de métier’ (craftsmen) in French-speaking history of work. It examines whether this term corresponds to the social representations preserved in ancient literature and philosophy, by considering the boundaries of the craft world, which is first defined by its border with agriculture. Such a division leaves aside many dubious cases, but digs deep into ancient attitudes, so that the crafts are credited with reverse characteristics of agriculture. However, the non-agricultural occupations are far from all belonging to the so‑called technè, so the boundaries drawn up by authors between these activities will be defined, in order to show how this economic domain is supposed to derive its coherence from an artisanal core.